Post-traumatic stress disorder among healthcare workers during the COVID-19 pandemic in Italy: Effectiveness of an eye movement desensitization and reprocessing intervention protocol - Fernandez, Isabel; Pagani, Marco; Gallina, Eugenio (Frontiers in psychology, 2022)
The Coronavirus 2019 (COVID-19) pandemic represents one of the most catastrophic events of recent times. Due to the hospitals' emergency situation, the population of healthcare workers was the most affected. Healthcare workers who were exposed to COVID-19 patients are most likely to develop psychological distress and post-traumatic stress disorder (PTSD). The present study aimed at investigating PTSD in a sample of Italian healthcare workers during this outbreak and to evaluate the effectiveness of the Eye Movement Desensitization and Reprocessing (EMDR) Therapy with this population.AimThe Coronavirus 2019 (COVID-19) pandemic represents one of the most catastrophic events of recent times. Due to the hospitals' emergency situation, the population of healthcare workers was the most affected. Healthcare workers who were exposed to COVID-19 patients are most likely to develop psychological distress and post-traumatic stress disorder (PTSD). The present study aimed at investigating PTSD in a sample of Italian healthcare workers during this outbreak and to evaluate the effectiveness of the Eye Movement Desensitization and Reprocessing (EMDR) Therapy with this population.A total of 744 healthcare workers were included. 587 healthcare workers were treated with EMDR, while the other 157 were not treated. Participants were asked to provide sociodemographic information; the post-traumatic symptomatology was evaluated through Impact of Event Scale-Revised (IES-R) and to investigate the level of intensity of emotional activation was used The Emotion Thermometer (THERMO) at two time points (pre-post treatment).MethodsA total of 744 healthcare workers were included. 587 healthcare workers were treated with EMDR, while the other 157 were not treated. Participants were asked to provide sociodemographic information; the post-traumatic symptomatology was evaluated through Impact of Event Scale-Revised (IES-R) and to investigate the level of intensity of emotional activation was used The Emotion Thermometer (THERMO) at two time points (pre-post treatment).The results obtained between EMDR treatment and non-EMDR treatment were evaluated on only 2 hospitals. Treatment group n = 68 vs. waitlist non-treatment group n = 157. All scores pre- and post-EMDR decreased significantly (p < 0.001) showing an evident effect of EMDR. The differences between pre- and post-treatment of the IES-R scores of subjects in which EMDR was performed as compared to the scores pre- and post-12 weeks of waiting list subjects in which it was not performed were significantly different (p < 0.001).ResultsThe results obtained between EMDR treatment and non-EMDR treatment were evaluated on only 2 hospitals. Treatment group n = 68 vs. waitlist non-treatment group n = 157. All scores pre- and post-EMDR decreased significantly (p < 0.001) showing an evident effect of EMDR. The differences between pre- and post-treatment of the IES-R scores of subjects in which EMDR was performed as compared to the scores pre- and post-12 weeks of waiting list subjects in which it was not performed were significantly different (p < 0.001).The emergency situation did not provide an opportunity to explore further aspects that would have been important for research. One limitation is the use and analysis of only two standardized tests. In addition, other psychopathologies were not investigated as outcome measures. A limitation is the comparison of subjects treated online and de visu. Although the protocol used was the same, the mode of intervention may have influenced the results. In addition, the effectiveness of EMDR treatment was only evaluated at two time points (pre-post) with no possibility of follow-up and the lack of a control group.LimitationThe emergency situation did not provide an opportunity to explore further aspects that would have been important for research. One limitation is the use and analysis of only two standardized tests. In addition, other psychopathologies were not investigated as outcome measures. A limitation is the comparison of subjects treated online and de visu. Although the protocol used was the same, the mode of intervention may have influenced the results. In addition, the effectiveness of EMDR treatment was only evaluated at two time points (pre-post) with no possibility of follow-up and the lack of a control group.The findings of the present study suggest that healthcare workers were at high risk of developing PTSD when confronted with COVID-19 outbreak and suggest the importance of psychological support during this humanitarian emergency.Discussion/conclusionThe findings of the present study suggest that healthcare workers were at high risk of developing PTSD when confronted with COVID-19 outbreak and suggest the importance of psychological support during this humanitarian emergency.